Building in Assyria a philological perspective - Tudeau, Johanna (Wiesbaden Harrassowitz Verlag, 2019)
Cover -- Title Page -- Copyright -- Table of Contents -- Body -- ABBREVIATIONS -- PREFACE -- INTRODUCTION -- 1 The setting -- 2 The questions -- 3 The sources -- a. Royal inscriptions -- b. State archives -- c. Omens -- 4 The methodology -- 5 Previous studies -- 1 PLANNING -- 1.1 The motivations -- kapādu, libbu, uznu, kabattu -- 1.1.1 Relationship with the divine -- 1.1.2 Finding inspiration and ratification for building projects -- 1.2 Creative process: design and measure -- 1.2.1 Concepts -- iṣratu -- šiṭru -- gišḫurru -- mišiḫtu -- šikittu -- 1.2.2 Models -- 1.2.3 Specifications -- itti šiṭir burūmê -- kīma simātīšu labirāti -- eli ša ūmē pāni/eli ša maḫri -- pān [D/PN] maḫir -- ultu ūmē panû -- 1.2.4 Numbers and precision -- 1.3 Technical process -- 1.3.1 Graphics -- līṭu -- 1.3.2 Design and function -- 1.3.3 Measurements -- 1.4 Administrative process -- 1.4.1 Adapting administrative requirements to time constraints -- 1.4.2 Managing human and material resources on the construction site -- tikpu/tikbu/tibku, pilku -- 1.5 Planning as moral act -- 1.6 Planning experts -- 1.7 Omen series -- 2 SITE SELECTION AND FOUNDATION -- 2.1 Site selection (general) -- 2.1.1 Selecting new sites: building from scratch -- qaqqaru, erṣetu, eperu -- šubtu/mūšabu, maškanu -- 2.1.2 Selecting ancient sites: building on ancient foundations -- ašru -- 2.2 Foundation process (general) -- 2.2.1 The foundations -- uššu (URU₄), išdu, temennu (TEMEN), duruššu -- uššu vs. temennu -- dannatu, asurrû, pīlu -- 2.2.2 Foundation rituals -- libittu maḫrītu -- sikkatu -- temennu, narû, ṭuppu, musarû/muššaru, šiṭir šumi/šumu šaṭru -- 2.2.3 Divine agency -- 3 MATERIALS -- 3.1 Bricks -- 3.1.1 Types of bricks, terminology and use -- libittu (SIG₄), agurru (SIG₄.AL.UR₃.RA), ebirtu (SIG₄.AL.UR₃.RA) -- 3.1.2 Stages of manufacture and distribution -- tikpu/tikbu/tibku, pilku.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Hochschulschrift